Peningkatan Sikap Nasionalisme Siswa Sekolah Dasar melaui Permainan Tradisional di SDN Darawolong III - Salsabila, Wulandari; Pratiwi, Maryati; Ramadhan, Muhammad Majid (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In this era of globaization, development is happening rapidly, and as Indonesian citizens, we have a duty to instill and uphold the spirit and attitude of nationaism. Loca culture is increasingly eroded by the impact of globaization. This is in line with concerns from partners about the low level of nationaism among children, as evidenced by their lack of knowledge about traditiona games as part of the loca cultura heritage. Therefore, in the current era of globaization, there is a need for a solution to enhance children's nationaism, which is by providing services to improve children's nationaism through traditiona games, such as rubber games, grobak sodor or gaa asin, and kotak pos. This activity will be carried out in December, specificaly on Thursday, the 27th of 2023, offline by playing traditiona games directly with 27 children at SDN Darawolong III Karawang. The results of this activity show that 100% of the children have an increasingly improved sense of nationaism, as evidenced by the development of character vaues needed in nationa life such as honesty, patience, responsibility, discipline, cooperation, and mutua respect. In addition, the children's desire to continue learning other traditiona games aso reflects their nationaist attitudes. The results are evauated through a Q&A session during the activity.